On Global Exponential Stability of Discrete-Time Hopfield Neural Networks with Variable Delays - Qiang Zhang; Xiaopeng Wei; Jin Xu (Discrete Dynamics in Nature and Society)
Global exponential stability of a class of discrete-time Hopfield neural networks with variable delays is considered. By making use of a difference inequality, a new global exponential stability result is provided. The result only requires the delay to be bounded. For this reason, the result is milder than those presented in the earlier references. Furthermore, two examples are given to show the efficiency of our result.